Viewpoint: Fieldwork in Ecology as a Form of Experiential Learning- First-year university students' experiences of a short experiential learning intervention - Michele Stears (Environmental Association of Southern Africa, 2010)
The small-scale research study reported on in this Viewpoint paper was conducted to determine the extent to which experiential learning in the form of fieldwork contributes to learning in Biology. The participants in the study were 36 first-year students registered for a module on Ecology. The conceptual framework that framed the study is experiential learning, which proposes that students learn more effectively through firsthand experience. The methodological approach to this study was interpretive as it attempted to interpret students' responses to a survey as well as interview. It also attempted to determine whether students believed the fieldwork experience benefited them. The findings suggest that students who have very little prior experience of fieldwork do not benefit significantly with regard to understanding of scientific concepts, as is evident from students' performance in the module. While a substantial number of students indicated in the questionnaire that they benefited from experiential learning, the benefits appear to be largely in the affective domain, rather than in the cognitive domain. The findings have implications for the expectations we have of experiential learning in first-year Biology courses. The paper is published as a Viewpoint paper, as the views developed through this small-scale study can be further analysed and tested through further research. It was a useful 'first step' in exploring a complex topic, that if it is to be fully understood would require further research into the issues raised by this small-scale study.